Modern mechanisms for the protection of women's rights - Charos Ruslanbek qizi Rustamova; D.Sh. Umarkhanova (Genius Journals, 2023)
In this chapter, we will discuss the current mechanisms that protect women's rights. As we indicated in the previous chapter, the ONN has created documents according to which women's rights will be protected. The question arises, why? The fact is that women themselves cannot receive protection at the national level and therefore need international protection. Unfortunately, when forming human rights and the documents that enshrine it, the developers avoided gender equality issues and drafted laws with greater opportunities for men. But it is worth noting that according to article 2 of the International Covenant on Civil and Political Rights, it states that the State respected and ensured to all persons on its territory the rights granted to them without any distinction based on race, skin color, gender, language and other status. Consequently, by infringing on the rights of every woman, countries violate the aforementioned Covenant.
Keywords: woman; aforementioned; language; infringing